Effectiveness of the Surgical Safety Checklist in Correcting Errors: A Literature Review Applying Reason's Swiss Cheese Model. (25th June 2014) - Collins, Susan J.; Newhouse, Robin; Porter, Jody; Talsma, AkkeNeel
Abstract: Approximately 2, 700 patients are harmed by wrong‐site surgery each year. The World Health Organization created the surgical safety checklist to reduce the incidence of wrong‐site surgery. A project team conducted a narrative review of the literature to determine the effectiveness of the surgical safety checklist in correcting and preventing errors in the OR. Team members used Swiss cheese model of error by Reason to analyze the findings. Analysis of results indicated the effectiveness of the surgical checklist in reducing the incidence of wrong‐site surgeries and other medical errors; however, checklists alone will not prevent all errors. Successful implementation requires perioperative stakeholders to understand the nature of errors, recognize the complex dynamic between systems and individuals, and create a just culture that encourages a shared vision of patient safety.